The Perception of the People of Aceh Besar Towards Syekh Abdullah Kan’an: Persepsi Masyarakat Aceh Besar Terhadap Syekh Abdullah Kan’an - Husda, Husaini; Safira, Yulia; Anwar (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
Syekh Abdullah Kan'an was a Palestinian cleric and is considered pioneer of Islam to Aceh Besar. Apart from being a scholar, he is also an entrepreneur and an expert in agriculture, especially pepper. He played a role in spreading pepper in Aceh, so he is called the father of Aceh pepper. The aim of this research is to determine the perception of the people of Desa Lampeneu’eun, Aceh Besar, regarding Syekh Abdullah Kan'an as the father of Aceh pepper and to examine his role in the spread of pepper in Aceh. This research is qualitative research. Data were collected through observation, interviews, and documentation studies. The findings suggest that Syekh Abdullah Kan'an, better known as Teungku Chik Lampeneu'eun, was born around 400-450 H/1012-1059 AD. The name Abdullah was given by his parents who came from Kan'an, Palestine, and were the first Mufti of the first Sultanate in Aceh. He was the figure who first introduced pepper seeds to the Aceh region. This success led pepper to become an important crop in Aceh. As a cleric, he is revered as a Tengku with blessings, and his reputation is well-known among local people and beyond the region.